Examination of phase changes in the CuAl high-temperature shape memory alloy with the addition of a third element - Kok, Mediha; Ata, Sahin; Yakinci, Zehra Deniz; Aydogdu, Yildirim (Springer, 2018)
In the present study, a ternary CuAl-based alloy was produced by adding 2% chromium, niobium, titanium and hafnium instead of 2% copper from the Cu88Al12 (% in mass) shape memory alloy, and the phase changes in the alloy were examined. As a result of the X-ray analyses performed at room temperature, the alpha phase, which is rich in copper, was detected in the main sample, i.e., the Cu88Al12 alloy, and the beta (1)(1) and gamma (A +/-)(1) phases were detected in the four of the Cu86Al12Cr2, Cu86Al12Nb2, Cu86Al12Ti2 and Cu86Al12Hf2 alloys. All of phases were clearly seen in SEM images. As a result of the mapping performed during chemical analysis, it was observed clearly that there appeared a precipitation phase in the Cu86Al12Cr2, Cu86Al12Nb2, Cu86Al12Ti2 alloys due to the additions. It was also observed that the additions were effective in forming a martensite phase in the Cu88Al12 alloy. In differential scanning calorimetry (DSC) measurements, which were taken to support these measurements, no martensitic phase transformations were detected in dual primary alloy (Cu88Al12); however, a clear martensite phase transformation was detected in ternary alloys (Cu86Al12Cr2, Cu86Al12Nb2, Cu86Al12Ti2 and Cu86Al12Hf2) in the first DSC measurement. Then, when the DSC cycle was applied to the ternary alloy, both the austenite transformation and martensite transformation temperatures were clearly seen, and it was claimed that all the alloys showed high-temperature shape memory alloy properties.
Keywords: CuAl-based; Element addition; Cu-rich phase; DSC cycle; High-temperature shape memory (HTSM)